Book Review: Teaching Business Sustainability Volume 2: Cases, Simulations and Experiential Approaches by Chris Galea. (25th April 2008) - Welford, Richard
Teaching Business Sustainability. Volume 2: Cases, Simulations and Experiential Approaches, by Chris Galea. Canada, Saint Francis Xavier University, 2007. 208pp. ISBN 978-1-874719-73-1